Antibiogram and susceptibility pattern of bacterial isolates of urinary tract infection among children and adolescents at a tertiary care hospital - Arshad, Salman; Rasheed, Shahid; Hussain, Mudassar; Munir, Saqib; Qamar, Nadia; Sattar, Abdul (Infectious Diseases Journal of Pakistan, 2024)
Background: UTI is one of the major causes of morbidity among children and adolescents in developing countries like Pakistan, where precise knowledge of causative micro-organisms and their antimicrobial susceptibility patterns remains inadequate. To identify common organisms involved in urinary tract infection and their antimicrobial sensitivity patterns among children & adolescents. Material and Methods : This retrospective descriptive study was conducted on urine cultures reports of children less than 18 year presented with suspected UTI in Allama Iqbal Memorial Teaching Hospital between the periods of January 2020 to December 2022 were taken. Urine sample cultured on CLED agar plates, micro-organism were identified by performing their morphological & biochemical tests. Results: Urine culture reports of 500 patients of age <18 years with suspected UTI were collected, out of which 102 were positive. The most common age for UTI was 5-11 years. The ratio of boys and girls was 30 and 72 respectively. Both Gram-negative and Gram-positive bacterial species were recovered. The ratio of gram negative to gram positive was 94 and 8 respectively. Among Gram-negative bacterial species, E. coli was the most common organism. Antimicrobial susceptibility pattern of E. coli showed that susceptibility to commonly prescribed drugs as follows Gentamicin (80%), co-amoxiclav (52%), Trimethoprim- Sulfamethoxazole (19%), Cephalosporin’s (8%), and Amoxicillin (5%). Susceptibility to Nitrofurantoin & Fosfomycin was 80% and 63% respectively. Conclusion: E.coli was the most common organism Isolated. Co-amoxiclav, Nitrofurantoin and Fosfomycin have good susceptibility profile among the oral drugs and Gentamicin has high susceptibility among injectables. Keywords: Urinary tract infection, Antibiotic sensitivity, Urine culture